State Anxiety Impairs Proactive but Enhances Reactive Control - Yang, Youcai; Miskovich, Tara A.; Larson, Christine L. (Frontiers in Psychology, 2018)
Cognitive control is a construct that prioritizes how we process stimuli and information to flexibly and efficiently adapt to internal goals and external environmental changes. The Dual Mechanism of Control (DMC) theory delineates two distinct cognitive control operations: proactive control and reactive control. Anxiety has been posited to differentially affect proactive and reactive control, due to its influence on working memory and attention allocation. However, no study has yet directly compared the influence of anxiety on proactive and reactive control in the same individuals. In this study, we examined how state anxiety affected proactive control, using the AX-continuous performance task (AX-CPT), and reactive control, using the classic Stroop task. Based on theory and previous investigations, we expected that state anxiety would enhance reactive control but impair proactive control. Consistent with our predictions, we found that state anxiety, induced with a threat of shock manipulation, inhibited proactive control on the AX-CPT test, but increased reactive control in the Stroop task. Anxiety may impair proactive control in contexts requiring goal maintenance by occupying limited working memory capacity, whereas it may enhance reactive control via facilitated attention allocation to threat and engaging the conflict monitoring system to quickly modify behavior.